Characteristics of Apparent Diffusion Coefficient and Time Intensity Curve in AdvancedMagnetic Resonance Imaging of Malignant Soft Tissue Tumors - Agus Jati Waluyo; Sri Andreani Utomo; Rosy Setiawat (Institute of Medico-legal Publications Pvt Ltd, 2021)
Malignant soft tissue tumors are usually identified and characterized by conventional magnetic resonance imaging (MRI) due to its high resolution on soft tissues. However,combinationof advanced MRI and conventional MRI increases the accuracy. This study was conducted to assess the characteristics of apparent diffusion coefficient(ADC) and time intensity curve (TIC) in dynamic contrast-enhanced MRI (DCE-MRI) in malignant soft tissue tumors. A cross-sectional study was conducted inDr. Soetomo Hospital, Surabaya, Indonesia. Demographic and clinical data, theclassification of malignant soft tissue tumor, histopathological examination results, ADC value, and TIC of DCE-MRI were collected.Between 1st January2018 and 30thAugust 2020, 30 malignant soft tissue tumors were included of which the most common malignantsoft tissue tumorsoccurred in those who were older than 50 year (30.0%) and located in the femur (33.3%). The most common tumor was synovial sarcoma (23.3%) and undifferentiated pleiomorphic sarcoma (20.0%). Type 4 and 3 of TIC were found in 92.0% and 8.0%, respectively. The overall mean of ADC and steepest slope were 0.84x10-3±0.14x10-3mm2/sand 15.8%±19.9%, respectively. The highest and the lowest mean ADCwas observed in squamous cell carcinoma and squamous cell carcinoma, and malignant peripheral nerve sheath tumor (MPNST), respectively. In contrast, the highest and the lowest steepest slopewas found in MPNST and squamous cell carcinomawith 75.43% and 2.45%, respectively.In conclusion, information of TICparameters such as ADCvalue and steepest slope might potentially be used in determining the histopathologic types of malignant soft tissue tumors.